Sosialisasi Bahaya Paparan Mikroplastik Terhadap Kesehatan Pangan Masyarakat - Ischak, Netty Ino; Aman, La Ode; Arviani, Arviani (Damhil: Jurnal Pengabdian kepada Masyarakat, 2023)
Microplastics pose a significant threat to both aquatic ecosystems and human well-being. This study endeavors to conduct a community engagement initiative focused on microplastic hazards in Molotabu Regency, with the goal of raising public awareness and fostering sustainable behavior change in plastic waste management. Microplastic pollution has emerged as a concerning issue, posing potential risks to food safety and public health. This research aims to conduct a socialization program on the hazards of microplastic exposure to food safety in the community of Molotabu Village. Using a participatory approach, this socialization program involves various stakeholders, including local communities and students. The socialization activities encompass informative presentations, interactive discussions, educational campaigns, and practical demonstrations to raise awareness about the adverse effects of microplastics on food safety. The results of this community engagement are expected to serve as valuable guidance for authorities and the local community to enhance awareness about the hazards of microplastics and promote sustainable behavior change in plastic waste management.